Absorption coefficient of nearly transparent liquids measured using thermal lens spectrometry - Cabrera, H.; Marcano, A.; Castellanos, Y. (Condensed Matter Physics, 2006)
We use an optimized pump-probe mode-mismatched thermal lens scheme to determine the optical absorption
coefficient and thermal diffusivity of ethanol, benzene, acetone, methanol, toluene and chloroform. In this
scheme the excitation beam is focused in the presence of a collimated probe beam. The agreement between
experimentally obtained results and values reported in the literature is good.